Technology of studies of throw with both hands from а breasts in basketball - Лаврін, Г. З. (Physical Education Theory and Methodology, 2012)
In the article technology of studies of throw with both hands from а breasts in basketball. Certainly basic pre-conditions for mastering of reception of game; the system of concrete tasks and neat facilities is formed for their decision; certainly typical errors and ways of their prophylaxis and removal; controls and self-control are offered.